The effectiveness of digital technology-based Otago Exercise Program on balance ability, muscle strength and fall efficacy in the elderly: a systematic review and meta-analysis - Zihao He; Hua Wu; Guanggao Zhao; Yiming Zhang; Chao Li; Yachen Xing; Anjie Xu; Junchao Yang; Ronghui Wang (BMC Public Health)
Abstract Objective To explore the impact of the digital implementation of the Otago Exercise Program (OEP) on balance ability (static and dynamic), muscle strength, and fall efficacy in elderly people; and analyze different potential influencing factors in subgroups to find the most suitable training plan. Methods EBSCO, PubMed, Web of Science, and China Knowledge Network databases (core) were searched up to August 1, 2023. Experimental studies of implementing OEP based on digital technology to improve outcomes related to falls in the elderly were included. Bias risks were assessed using the Cochrane collaboration tool. Meta-analysis was performed to assess the pooled effect of balance ability (static and dynamic), muscle strength, and fall efficacy using a random effects model. Subgroup analyses were conducted to examine the potential modifying effects of different factors (e.g., training period, frequency, duration, age). Results Twelve articles were included from the literature, including 10 randomized controlled trials, one single-group quasi-experimental study, and one case report. Digital technologies used in the studies were categorized into three types: (1) online interventions (Zoom, WeChat), (2) recorded videos (via computers, TVs, DVDs), and (3) wearable technologies (motion sensors, augmented reality systems). The implementation of OEP based on digital technology showed significantly improved on static balance (SMD = 0.86, 95% CI 0.35–1.37), dynamic balance (SMD = 1.07, 95% CI 0.90–1.24), muscular strength (SMD = 0.43, 95% CI 0.17–0.69), and fall efficacy (SMD=-0.70, 95% CI -0.98, -0.41); Subgroup analysis by period ‘≥12 weeks’, frequency ‘≥3 times/week’, and duration ‘≤45 minutes per session’, respectively, showed significant improvements on static balance (SMD = 0.73, 95% CI 0.21–1.25; SMD = 0.86, 95% CI 0.35–1.37; SMD = 1.10, 95% CI 0.31–1.89), dynamic balance (SMD = 1.08, 95% CI 0.88–1.28; SMD = 1.01, 95% CI 0.93–1.27; SMD = 1.07, 95% CI 0.89–1.25), muscle strength (SMD = 0.43, 95% CI 0.10–0.75; SMD = 0.54, 95% CI 0.30–0.77; SMD = 0.53, 95% CI 0.19–0.87), and fall efficacy (SMD=-0.75, 95% CI -1.39, -0.11; SMD=-0.70, 95% CI -0.98, -0.41; SMD=-0.74, 95% CI -1.10, -0.39). Conclusions OEP implemented through digital technology effectively enhances static and dynamic balance, muscle strength, and self-efficacy in older adults. A training regimen of 12 weeks or more, with sessions occurring three or more times per week for 30 to 45 min, appears to be an effective approach for improving these outcomes based on the available evidence from the included studies. Future research should prioritize specific digital technologies and target populations, employing high-quality research designs to further explore these interventions, and consider new technologies such as wearables, to assess changes in fall prevalence.